2008
DOI: 10.1159/000167795
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Administration of SMP-534 Ameliorates Renal Dysfunction in 5/6 Nephrectomized Rats

Abstract: Background/Aims: Chronic kidney disease (CKD) is the common cause of end-stage renal disease. Antihypertensive agents are clinically used to inhibit the progression of CKD. However, these agents cannot completely prevent progression to renal failure. We have previously reported that 5-chloro-2-{(1E)-3-[2-(4-methoxybenzoyl)-4-methyl-1H- pyrrol-1-yl]prop-1en-1-yl}-N-(methylsulfonyl)benzamide (SMP-534) improves renal disease and prevents the production of extracellular matrix in vitro. Additionally, SMP-534 inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
4
0

Year Published

2009
2009
2012
2012

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 44 publications
1
4
0
Order By: Relevance
“…The 5/6 Nx rat model is a well-established model of chronic kidney disease [19]. In agreement with this, we observed significant renal dysfunction in our 5/6 Nx rats, as indicated by increased urine albumin secretion, serum BUN and Scr levels.…”
Section: Discussionsupporting
confidence: 90%
“…The 5/6 Nx rat model is a well-established model of chronic kidney disease [19]. In agreement with this, we observed significant renal dysfunction in our 5/6 Nx rats, as indicated by increased urine albumin secretion, serum BUN and Scr levels.…”
Section: Discussionsupporting
confidence: 90%
“…20) In addition, it was also reported that single treatment with lisinopril significantly suppresses the progression of CKD in remnant kidney rats. 28) Because treatment with high dose of lisinopril or SMP-534 completely inhibits renal progression in 5/6Nx rats, we used suboptimal dose of SMP-534 and lisinopril to evaluate the combined effect of these agents.…”
Section: Discussionmentioning
confidence: 97%
“…[18][19][20] Accordingly, we have previously shown that combination therapy with SMP-534 and ARB, losartan, is effective in the treatment of diabetic nephropathy in diabetic db/db mouse. 21,22) However, we have not examined the effect of combination therapy with ACEI and SMP-534 on CKD models.…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, we have studied whether SMP-534 has beneficial effects on renal fibrosis. We have shown that treatment with SMP-534 inhibits accumulation of ECM in kidney of diabetic db/db mouse or 5/6 nephrectomized rats and ameliorates renal function (13,15). In the present study, we investigated whether SMP-534 has beneficial effects on pulmonary fibrosis in bleomycin-treated hamsters.…”
mentioning
confidence: 89%